Consumer Preferences for Integrated Marketing Communication Expert28 Cafe Kediri - Ricky Oktaf MESSAKH; Hilda Yunita WONO; Jessica Nathalia HERMAWAN (PT Keberlanjutan Strategis Indonesia, 2024)
Tourism is a major source of income for Indonesia, and Kediri is a popular destination for various types of tourism businesses. Expert28 Cafe Kediri, a local coffee shop brand, has successfully faced competition from other cafes by implementing effective marketing strategies. Integrated Marketing Communication (IMC) is the key approach used by Expert28 Cafe Kediri to attract potential customers. The cafe has implemented several IMC activities, including advertising, direct marketing, sales promotion, and digital marketing. To understand consumer preferences for these activities, a descriptive quantitative study was conducted using a questionnaire. The study involved 71 respondents who were Expert28 Cafe Kediri consumers familiar with the IMC activities. The analysis revealed that consumers preferred digital marketing the most, followed by advertising, direct marketing, and sales promotion. This study's findings provide valuable insight to help Expert28 Cafe Kediri enhance their marketing strategies by focusing on the most preferred IMC activities, particularly digital marketing.